Optimization of power system operation - Zhu, Jizhong, 1961- ([Piscataway, NJ] : IEEE Press ; Hoboken, New Jersey : Wiley, 2015)
"Optimization of Power System Operation applies the latest applications of new technologies to power system operation and analysis, including several new and important areas that are not covered in existing books: uncertainty analysis in power systems; steady-state security region analysis; optimal load shedding; and optimal reconfiguration of electric distribution networks. The book covers both traditional and modern technologies, including power flow analysis, steady-state security region analysis, security constrained economic dispatch, multi-area system economic dispatch, unit commitment, optimal power flow, smart grid operation, optimal load shed, optimal reconfiguration of distribution network, power system uncertainty analysis, power system sensitivity analysis, analytic hierarchical process, neural network, fuzzy theory, genetic algorithm, evolutionary programming, and particle swarm optimization, among others. New topics such as the wheeling model, multi-area wheeling, the total transfer capability computation in multiple areas, are also addressed. The application of renewable energy and operation of smart grid is also included in the book"--
"Addresses advanced methods and optimization technologies and their applications in power systems"--
""2.4 P-Q Decoupling Method """"2.4.1 Fast Decoupled Power Flow ""; ""2.4.2 Decoupled Power Flow without Major Approximation ""; ""2.5 DC Power Flow ""; ""2.6 State Estimation ""; ""2.6.1 State Estimation Model ""; ""2.6.2 WLS Algorithm for State Estimation ""; ""Problems and Exercises ""
Includes bibliographical references and index.
Print version record.
Keywords: Electric power systems -- Mathematical models; Mathematical optimization; Electric power systems -- Mathematical models; Mathematical optimization; TECHNOLOGY & ENGINEERING -- Power Resources -- General; TECHNOLOGY & ENGINEERING -- Mechanical; Electric power systems -- Mathematical models; Mathematical optimization; Electronic books; Electronic books